Suicide and self-injury outcomes for patients with comorbid psychiatric and physical health conditions. (February 2022) - Karnick, Aleksandr T.; Boska, Rachel L.; Caulfield, Nicole M.; Winchell, Robert; Capron, Daniel W.
Highlights: Psychiatric and physical comorbidity among suicide attempts appear at trauma units. Psychiatric comorbidity is associated with less severe suicide outcomes. Physical health conditions are not associated with worse suicide outcomes. Psychiatric conditions are unidentified, present near an attempt, or not present in attempters. Trauma units provide a unique opportunity for suicide intervention strategies. Abstract: Suicide is a transdiagnostic public health issue that affects nearly all psychiatric disorders, individuals without a mental health diagnosis, and individuals with physical health issues. We assessed the relationship between these variables and suicide outcomes using a novel epidemiological research paradigm. Data were collected from the National Trauma Data Bank. Participants included patients admitted to trauma units for suicide and self-injury ( n  = 13, 422). Patients were classified to one of four comorbid condition groups: no comorbidity, comorbid physical condition, comorbid major psychiatric condition, or multimorbidity (comorbid physical and psychiatric conditions). Multivariable logistic regression measured associations between comorbid condition and mortality and multivariable linear regression measured associations between comorbidity and injury severity. Mortality in patients with physical health comorbidity was not significant, but patients with psychiatric comorbidity or multimorbidity had significantly lower mortality than patients without either. No association between injury severity and comorbidity was detected. There were no differences in suicide mortality for individuals with a physical health comorbidity, but mortality was lower for individuals with a comorbid major psychiatric illness or multimorbidity. Since physical health conditions and psychiatric illness are associated with eventual suicide mortality, prevention strategies could target these populations at trauma units for suicide and self-injury admissions.